Evolving Poverty in Italy: Individual Changes and Social Support Networks - Serena Quarta (Societies, 2025)
Over the last 20 years, poverty has undergone profound changes, even affecting people who were once safe from the processes of impoverishment. Hidden under the guise of normal difficulties considered part of the natural course of life, it has lost its “occasional” connotation and has become “established” in people’s lives, causing new and dangerous trends. The article offers some reflections on how these dynamics have become particularly widespread in Italy, resulting in two types of poverty: cultural poverty, linked to the phenomenon of young NEETs (Not in Employment, Education, or Training), and working poverty. These types of poverty are linked and risk feeding off each other. On the one hand, poor cultural tools force young people to settle for low-paid jobs. On the other hand, poor-quality work, due to poor training, discourages people from pursuing education and training and traps poor workers in a situation of social stagnation. A possible tool to tackle these issues could be Responsible Welfare, which focuses on the person as a unique entity, implementing the resilience of individuals to promote self-esteem while also enhancing relational, social, and community resources.